2015
DOI: 10.1021/acs.langmuir.5b03240
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of Sessile Droplets on Slippery Liquid-Infused Porous Surfaces (SLIPS)

Abstract: Over the past decade, the most common approach to creating liquid shedding surfaces has been to amplify the effects of nonwetting surface chemistry, using micro/ nanotexturing to create superhydrophobic and superoleophobic surfaces. Recently, an alternative approach using impregnation of micro/nanotextured surfaces with immiscible lubricating liquids to create slippery liquid-infused porous surfaces (SLIPS) has been developed. These types of surfaces open up new opportunities to study the mechanism of evaporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(180 citation statements)
references
References 43 publications
7
173
0
Order By: Relevance
“…In our previous work on droplet evaporation from SLIPS surfaces, we have observed that a droplet will inherently have a very low contact angle hysteresis [37] and be highly mobile, typically moving when a surface is tilted from the horizontal by less than 1 o , due to the existence of the lubricating layer. Ensuring conditions in eq.…”
Section: 3slippery Liquid Infused Porous Surfaces (Slips)mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work on droplet evaporation from SLIPS surfaces, we have observed that a droplet will inherently have a very low contact angle hysteresis [37] and be highly mobile, typically moving when a surface is tilted from the horizontal by less than 1 o , due to the existence of the lubricating layer. Ensuring conditions in eq.…”
Section: 3slippery Liquid Infused Porous Surfaces (Slips)mentioning
confidence: 99%
“…In the present work, we propose a new method for SAW-induced droplet actuation, which is built on our understanding of SLIP surfaces [22,33,34,37,38]. In our case the infused liquid is chosen to be a lubricant oil and by designing the SLIP surface layer to be significantly thinner than the SAW wavelength, we ensure that little damping of the acoustic wave occurs by the lubricant in the SLIP layer.…”
Section: New Design Of Slips For Saw Microfluidicsmentioning
confidence: 99%
“…145°) is observed. The decrease of CA over time in the case of pure POFPMA is likely due to the evaporation of the water drop …”
Section: Resultsmentioning
confidence: 99%
“…Beyond antibiofouling and antithrombosis of medical devices/materials, slippery surface were applied to enhance the sensitivity of Raman scattering detection . It is well noted that LISS allow a constant contact angle evaporation (contact line pinning‐free evaporation) because of the high mobility and low hysteresis of the apparent contact line . By using slippery surface as a platform to enrich and delivery to molar level solutions (Figure ), researchers demonstrated ultrasensitive detection (down to the subfemtomolar level (<10 −15 mol L −1 )) of chemical and biological molecules (e.g.…”
Section: Emerging Biomedical Applications Of Bioinspired Slippery Surmentioning
confidence: 99%
“…[15c] It is welln oted that LISS allow ac onstant contact angle evaporation (contact line pinning-free evaporation)b ecause of the high mobility and low hysteresis of the apparent contact line. [55] By using slippery surface as ap latform to enrich and delivery to molar level solutions (Figure 12), researchers demonstrated ultrasensitive detection (down to the subfemtomolar level (< 10 À15 mol L À1 )) of chemical and biological molecules (e.g. thymine, adenine and BSA) and environmental contaminants in different fluids throughs lippery surface enhanced Ramans cattering and molecular sensing.…”
Section: Liss On Biomaterialsand Medical Devicesmentioning
confidence: 99%